2011
DOI: 10.1016/j.ijsu.2011.07.430
|View full text |Cite
|
Sign up to set email alerts
|

Dye assisted lymphatic sparing subinguinal varicocelectomy. A prospective randomized study

Abstract: Subinguinal varicocelectomy using combination of optical magnification and lymphatic staining (methylene blue) offers simple and quick preservation of the draining lymphatic vessels and avoids secondary hydrocele formation. ClinicalTrials.gov ID: NCT01259258.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…Studies have shown that dyeassisted lymphatic-sparing techniques have lower hydrocele rates. [37][38][39] Although none of our patients required surgery for hydrocele, it has been reported that repeated aspirations of hydrocele fluid are not curative and that Jaboulay hydrocelectomy is often necessary. 36 It was also found that the mean time to detect palpable varicocele was 2 years after operation.…”
Section: Discussionmentioning
confidence: 75%
“…Studies have shown that dyeassisted lymphatic-sparing techniques have lower hydrocele rates. [37][38][39] Although none of our patients required surgery for hydrocele, it has been reported that repeated aspirations of hydrocele fluid are not curative and that Jaboulay hydrocelectomy is often necessary. 36 It was also found that the mean time to detect palpable varicocele was 2 years after operation.…”
Section: Discussionmentioning
confidence: 75%
“…Several surgical techniques via high retroperitoneal, inguinal, microsurgical inguinal, and laparoscopic approaches have been reported, but with no most ideal treatment 2345. Although some reports indicated that the microsurgical varicocelectomy may be lead to a lower incidence of postoperative hydrocele formation, the operating time is considerably longer than that for other procedures 1112.…”
Section: Discussionmentioning
confidence: 99%
“…There are several treatment options including percutaneous embolization, inguinal varicocelectomy, subinguinal microscopic varicocelectomy, and laparoscopic varicocele ligation. However, the ideal treatment for varicocele is still controversial 2345. Laparoscopic varicocele ligation is regarded in recent years as a safe, effective, and minimally invasive method with the similar results to that of others 26…”
Section: Introductionmentioning
confidence: 99%
“…M.E. Abd Ellatif проведено лімфатичне мапування інтраопераційно і отримано успішніші післяопераційні результати, ніж після застосування виключно субінгвінальної мікрохірургічної варикоцелектомії [1].…”
Section: результати дослідження та їх обговоренняunclassified